EFFECT OF TRAINING LEG MUSCLE POWER ON THE ACCURACY AND SPEED OF SERVICE AS TAKRAW IN CENTRAL JAVA MAN PLAYERS - Tri Aji (Program Pascasarjana Universitas Negeri Jakarta, 2018)
This research looks for the effect of treatment of an exercise whether training is a power leg type of exercise jump to box with an incline bound has an effect on the speed and accuracy of the takraw service. The basis of this method is that experimentation is a research technique based on experiment by holding a preliminary test and a final test then tested for correctness. Research method is an absolute requirement of a study. The use of methods in scientific research must be precise and lead to the goal, provide accurate outlines and propose new conditions. In finding answers to this research, various methods such as survey, descriptive, correlation or experimental methods are used. In this study is to find whether there is a cause and effect relationship, in connection with which used in this research is the experimental method. Based on theF value calculated for the speed data of 5,612 <F table of 0.039 with a significance value of 0.05, which means that there is a difference in the increase in speed between the two groups after being given training, while for the accuracy data it is obtained Fcount = 0.621 with p value = 0.261> 0.05, which means that there is a difference in the increase in accuracy between the two groups after being given the exercise. Based on the results of the analysis, it provides an overview of training power leg using plyometrics with inclne bound and jump to box exercises that have an effect on increasing service speed and affect the accuracy of service.